l’euthanasie et la mort avec Dignité en Droit japonais - Prof. Dr. Katsunori Kai, (Journal international de bioéthique et d'éthique des sciences, 2010)
In Japan, there are no acts and, specific provisions or official guidelines on euthanasia, but recently, as I will mention below, an official guideline on “death with dignity” has been made. Nevertheless in fact, this guideline provides only a few rules of process on terminal care. Therefore the problems of euthanasia and “death with dignity” are mainly left to the legal interpretation by literatures and judicial precedents of homicide (Article 199 of the Criminal Code; where there is no distinction between murder and manslaughter) and of homicide with consent (Article 202 of the Criminal Code). Furthermore, there are several cases on euthanasia or “death with dignity” as well as borderline cases in Japan. In this paper I will present the situation of the latest discussions on euthanasia and “death with dignity” in Japan from the viewpoint of medical law. Especially, “death with dignity” is seriously discussed in Japan, therefore I focus on it.